Oncogenic DNA viruses found in salivary gland tumors. (December 2017) - Chen, Alyce A.; Gheit, Tarik; Stellin, Marco; Lupato, Valentina; Spinato, Giacomo; Fuson, Roberto; Menegaldo, Anna; Mckay-Chopin, Sandrine; Dal Cin, Elisa; Tirelli, Giancarlo; Da Mosto, Maria Cristina; Tommasino, Massimo; et al.
Highlights: Polyomavirus DNA was detected in normal and neoplastic salivary gland tissue. Beta human papillomaviruses are possibly associated with salivary malignancies. Herpesvirus, specifically EBV1, DNA was highly prevalent in Warthin's tumors. Abstract: Background: Previous investigations studying the association of DNA viruses with salivary gland tumors (SGTs) have led to conflicting results. The aim of this study was to determine the prevalence of different DNA viruses by using a highly sensitive assay in a multi-center series of over 100 fresh frozen salivary gland samples. Methods: DNA was isolated from 84 SGTs (80 parotid tumors and 4 submandibular gland tumors) and 28 normal salivary tissue samples from 85 patients in Northeast Italy. Using a highly sensitive type-specific multiplex genotyping assay, we analyzed the samples for the presence of DNA from 62 different viruses including 47 papillomaviruses, 10 polyomaviruses, and 5 herpesviruses. Results: We observed a high prevalence of beta human papillomavirus DNA in malignant tumors. In contrast, polyomavirus DNA was present in benign, malignant, and non-tumor control samples. Most striking was the significant distribution of herpesvirus DNA in the SGT samples, in particular the high prevalence of Epstein-Barr type 1 and type 2 DNA in Warthin's tumor samples. Conclusion: Our data provides evidence for the presence of DNA viruses in SGTs. Mechanistic studies are needed to further attribute tumor formation to these viruses.